(untitled) (Anuário Antropológico, 2023)
The whole practice of an anthropology of the contemporary – and the questions that arise from this practice – are remarkably "condensed," so to speak, in this article by Gustavo Lins Ribeiro (GLR). The contemporary world that any anthropologist may set out to study is defined not through a monographic and myopic gaze (typical to the ethnological tradition that still forms part of our legacy, after all), but through an exploration of the connections between ethnographic observation and diverse levels of constraints and forces – connections that are too quickly summarized by the local/global formula. It seems to me more precise to say that this contemporary world may be understood through a relationship between situation and context. The situation is what I can observe and experience directly; the context is what I cannot see immediately, but can grasp through different procedures, more or less concrete or abstract, more or less empirical or theoretical. What mediates between the two? This is my understanding of the question that occupies GLR in his article. It is rich in the domain of the self-reflexivity and epistemology of anthropology – indeed, of any field-based social science. All the article’s proposals and observations are fascinating and inspirational. They inspire me to think with them, to question, compare and develop the author’s ideas. In this commentary, I shall mention just a few of the avenues for further study suggested by the article, in light of my own practice.